Դարձվածային միավորները Երեւանի խոսակցական լեզվում - Լուսինե Ղամոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Один из самых характерных слоев словарного состава разговорного языка Еревана - фразеология. One of the most characteristic layers of the vocabulary of the colloquial language of Yerevan is phraseology.
Keywords: Language and Literature